A Fixed Point Theorem for Monotone Functions equivalent to Browers theorem - Håkan Persson (Örebro University School of Business, 2005)
A Fixed Point Theorem for Monotone Functions equivalent to Browers theorem
Keywords: C65; 330; Increasing function; Fixed point